(untitled) (Revista de Investigaciones Universidad del Quindío, 2019)
Coffee is one of the most consumed beverages in the world, and Colombia has exceptional qualities for its cultivation, production and industry. The objective was to evaluate using a tasting panel, the quality in a cup of four varieties of coffee, of colombian origin (exactly from the Department of Quindío), of the species Coffea arabica L. A quantitative - descriptive study was carried out, supported in an experimental design, the selected varieties: Geisha, pink Bourbon, Moka and Castillo were chosen, the first three are special coffees and the last is a seed, of superior quality, comparable to the others. For the cup evaluation, different levels of roasting were performed. It was found that for the Geisha variety obtained the highest score in its three levels of roasting, and among these, the level of low roasting highlighted its qualities. It´s concluded that for the varieties used, the variety of coffee influences the cup quality.